Improving Student Science Literacy Ability Using the Frayer Model Diagram in Class X Global Warming Materials - U’ud Efendi (Tinta Emas Publisher, 2023)
This research aimed to describe the application of Frayer Diagrams to students’ literacy ability in understanding global warming issues. This research apllied a pre-experimental design with one group pretest-postest concept involving 33 students of class X-4 in SMA Negeri 5 Jember. The data of this research were collected from the objective written test which was analyzed by descriptive – quantitative method. The result of this research showed that the average score of science literacy ability of students on the pretest was 30,00, while on the post test was 68,18, with the increasing number of students, literacy ability showed by N-gain value 0,56 which was categorized as medium level. Based on this research, it can be concluded that the application of frayer diagrams can enhance student’s literacy ability to understanding global warming issues.